The Influence of Job Insecurity and Job Satisfaction on Turnover Intention PT. Bank Pembiayaan Rakyat Syariah Dinar Ashri East Lombok Branch - Elda Zita Sismi; Sulaimiah Sulaimiah (Lafadz Jaya Publisher, 2023)
This study focuses on the impact of job uncertainty and job satisfaction on employee turnover tendencies working at the East Lombok branch of PT. Bank Sharia Dinar Ashri People's Financing Bank. The aim of this research is to investigate the impact of job uncertainty and the level of job satisfaction on the possibility of employee turnover. This type of research is related and uses a number-based approach. Data collection was carried out by means of a census. The population and respondents in this study included 35 employees from PT. Sharia People's Financing Bank Dinar Ashri. In this research, the analytical tool used is multiple linear regression with the help of SPPS version 16.0 software. The findings from the analysis show that (1) job uncertainty factors have a positive and significant impact on employee turnover tendencies (2) while job satisfaction has a negative and significant impact on turnover intention.